Untranslated physics literature - Esteban Zárate Mejía; Brenda Yisel Díaz Hernández (Enletawa Journal)
This study examines how untranslated English physics literature affects Spanish – speaking physics students’ academic experiences and educators’ professional practice at a southeastern Mexican university. The highlighted aspects were challenges in comprehension, performance, and research participation. A qualitative case study design was implemented while the data was recollected through semi-structured interviews with educators and a customized questionnaire for students. Then the data was analyzed by thematic analysis, aided with Atlas.ti version 25 software to develop the results. The findings revealed that English only resources create significant comprehension barriers, hinder academic achievement, also complicate research engagement. The participants managed these challenges by using translation tools, collaborative strategies and their own bilingual materials. While English increases scientific visibility, its dominance restricts equity along with inclusion for non – English speakers. The study concludes that institutions should implement targeted English support and language immersion to improve access as well as participation in global scientific discourse.